Neuroimmune Aspects of Sjogren’s Syndrome: Role of VIP/VPAC System in Immune and Salivary Gland Epithelial Cell Function - Vanesa, Hauk; Mario, Calafat; Esteban, Grasso; Laura, Fraccaroli; Daniel, Paparini; Rosanna, Ramhorst; Leiros Claudia, Perez (Current Pharmaceutical Design, 2014)
Sjogren’s syndrome (SS) is a chronic inflammatory disease characterized by salivary and lacrimal gland dysfunction although extraglandular manifestations are also found. Suitable study models and in vitro cell culture designs are used to approach SS pathogenic mechanisms. Cellular and molecular pathways involved in gland homeostasis loss and the autoimmune response are focused in the search of novel drug targets and biomarkers. Vasoactive intestinal peptide (VIP) has trophic, pro-secretory and immunomodulatory effects in several chronic and autoimmune disease models. Here we review evidence pointing to its role as an endogenous modulator of gland homeostasis at early stages of the disease. Particularly, mechanisms involving VIP/VPAC system in the course of salivary function impairment in the non obese diabetic (NOD) mouse model of Sjögren’s syndrome are described.
Keywords: Vasoactive intestinal peptide – Sjogren Syndrome – Salivary epithelial cells